Insulin impairs the maturation of chondrocytes in vitro - E.S. Torres; C.V. Andrade; E.C. Fonseca; M.A. Mello; M.E.L. Duarte (Brazilian Journal of Medical and Biological Research, 2003)
The precise nature of hormones and growth factors directly responsible for cartilage maturation is still largely unclear. Since longitudinal bone growth occurs through endochondral bone formation, excess or deficiency of most hormones and growth factors strongly influences final adult height. The structure and composition of the cartilaginous extracellular matrix have a critical role in regulating the behavior of growth plate chondrocytes. Therefore, the maintenance of the three-dimensional cell-matrix interaction is necessary to study the influence of individual signaling molecules on chondrogenesis, cartilage maturation and calcification. To investigate the effects of insulin on both proliferation and induction of hypertrophy in chondrocytes in vitro we used high-density micromass cultures of chick embryonic limb mesenchymal cells. Culture medium was supplemented with 1% FCS + 60 ng/ml (0.01 µM) insulin and cultures were harvested at regular time points for later analysis. Proliferating cell nuclear antigen immunoreactivity was widely detected in insulin-treated cultures and persisted until day 21 and [³H]-thymidine uptake was highest on day 14. While apoptosis increased in control cultures as a function of culture time, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL)-labeled cells were markedly reduced in the presence of insulin. Type II collagen production, alkaline phosphatase activity and cell size were also lower in insulin-treated cultures. Our results indicate that under the influence of 60 ng/ml insulin, chick chondrocytes maintain their proliferative potential but do not become hypertrophic, suggesting that insulin can affect the regulation of chondrocyte maturation and hypertrophy, possibly through an antiapoptotic effect.